Musculoskeletal and cutaneous sarcoidosis: exuberant case report - Natalie Haddad; Jayme de Oliveira Filho; Kassila da Rosa Nasser; Ana Maria França Corbett; Ana Carolina Franco Tebet; Mariana Lacerda Junqueira Reis (Sociedade Brasileira de Dermatologia, 2014)
Sarcoidosis is a multisystem granulomatous disease of unknown cause. The osteoarticular involvement in sarcoidosis is rare and is often associated with cutaneous and long-standing chronic multisystem disease. More common in black women, osseous sarcoidosis is difficult to diagnose, with an incidence of 3 to 13%. The most characteristic radiological clinical picture evidences rounded, well-defined cysts, with no periosteal reaction and without peripheral sclerosis. The small bones of hands and feet are the most frequently involved sites. This report aims to demonstrate a rare case of osteoarticular sarcoidosis with characteristic clinical presentation, and highlight the importance of detecting osteoarticular involvement in this pathology.